In Vitro Antibacterial Activity of Ethanolic Extract of Pasak Bumi (Eurycoma longifolia) root against Streptococcus Pyogenes - Naulita Turnip, Oktaviani; Urdha, Adyatma; Teresa, Astrid; Nawan, Nawan; Arleny, Ina (Media Farmasi: Jurnal Ilmu Farmasi, 2026)
Infectious diseases remain a major public health concern in Indonesia, particularly upper respiratory tract infections such as pharyngitis caused by Streptococcus pyogenes. The increasing incidence of antibiotic resistance highlights the need for alternative antimicrobial agents from natural sources. Eurycoma longifolia (pasak bumi) is a medicinal plant known to contain bioactive compounds with potential antibacterial properties. This study aimed to evaluate the in vitro antibacterial activity of Eurycoma longifolia root extract against Streptococcus pyogenes. This study used a true experimental design with a post-test only control group. Antibacterial activity was tested using the disc diffusion method on Mueller Hinton Agar (MHA). Seven groups were tested: five extract concentrations (5%, 10%, 15%, 25%, and 50%), a positive control (erythromycin), and a negative control (aquades). Data were analysed using one-way ANOVA (p < 0.05). The extraction yielded 2.67% extract. The results showed inhibition zone diameters of 0 mm (negative control) and 22.35 mm (positive control). The extract exhibited inhibition zones of 2.0 mm, 3.25 mm, 3.5 mm, 3.75 mm, and 5.42 mm at concentrations of 5%, 10%, 15%, 25%, and 50%, respectively. Statistical analysis indicated significant differences among treatment groups. In conclusion, Eurycoma longifolia root extract demonstrated concentration-dependent antibacterial activity against Streptococcus pyogenes, with effects classified as weak to moderate. These findings suggest its potential as a natural antibacterial agent, although further studies are needed to optimize its efficacy.